Required documents and recognition and enforcement of foreign divorce judgement: commentary to the judicial decree of the Provincial Court of Barcelona, of November 20, 2019 - Fernández Masiá, Enrique (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This paper analyzes the Judicial Decree of the Provincial Court of Barcelona about the required documents that have to file along the claim of recognition and enforcement of a divorce judgment obtained in Argentina, as provided for the Spanish Act on International Judicial Cooperation in Civil Matters.
Keywords: recognition; exequatur proceedings; required documents- international judicial; coo¬peration in civil matters